Percutaneous decannulation of peripheral veno-arterial extracorporeal membrane oxygenation using the Manta closure device - Emilio Arbas Redondo,; Sandra Ofelia Rosillo Rodríguez,; Clara Ugueto Rodrigo,; Juan Caro Codón,; Alfonso Jurado Román,; Raúl Moreno (REC: Interventional Cardiology (English Ed.))
To the Editor, In cardiac surgery intensive care unit (CICU) the use of short-term mechanical circulatory support is increasingly common, such as venoarterial extracorporeal membrane oxygenation (VA-ECMO). The implantation of this device is almost always peripheral and involves the cannulation of a large-bore femoral arterial access. For this reason, vascular complications are a very common finding in patients on peripheral VA-ECMO1 with decannulation being one of the most critical moments. Currently, there are 2 types of vascular closure devices widely used in the cath lab: suture-based devices, such as the ProGlide (Abbott Vascular, United States), and collagen plug devices, such as the Angio-Seal (Terumo Corporation, Japan) and the Manta (Teleflex, United States). The latter has been specifically designed for the closure of large-bore arteriotomies using an intra-arterial anchoring system and an extra-arterial collagen plug, and is marketed in 2 different sizes: 14-Fr (for 10-14-Fr introducer sheaths and holes with an external diameter of up to 18-Fr) and 18-Fr (for 15-18-Fr introducer sheaths and holes with an external diameter of up to 25-Fr). Evidence in the field of structural heart procedures with the Manta device is very extensive2 and there is increasing experience in closing the arterial access of mechanical circulatory support systems,3,4...